Performance Analysis of a Recycled Concrete Interfacial Transition Zone in a Rapid Carbonization Environment - Gongbing Yue; Peng Zhang; Qiuyi Li; Qianqian Li (Advances in Materials Science and Engineering)
Based on the characteristics of recycled concrete interface structures, a multi-interface reconstruction model was established. To study the microstructure evolution of the interfacial transition zone (ITZ) during the carbonization process of recycled concrete, the microstructure characteristics of the ITZ of C30, C40, and C50 grade recycled concrete and the mortar matrix before and after carbonization were studied through the microhardness tester and SEM. The results show that the microhardness values of the ITZ and the mortar matrix are obviously increased and that the width of the ITZ decreases, while the ITZ performance of the C50 grade recycled concrete is not significantly changed. The ITZ exhibits a large amount of granular CaCO3 after carbonization, the pores are refined, and microcracks are generated. Overall, there are significant differences in the microstructures between the ITZ and the mortar matrix before and after carbonization.